TRAGICAL LIMIARS OF THE FORMATION: RISKS IN THE TEACHING EXPERIMENTATION IN A WRITING STUDY (Fiep Bulletin - online, 2015)
This study goals to form teaching staff focusing the subjectivity production, so naturally come up some questions in the micro-politics program about how becoming a teacher? For this purpose, it was used a modern philosophical reference in a way that can be observed certain writers on their moments: Nietzsche, Foucault and Deleuze.
Keywords: teacher formation; subjectivity; field diary.